Chromosomal Evolution in Lower Vertebrates: Sex Chromosomes in Neotropical Fishes - Cioffi, Marcelo de Bello; Yano, Cassia Fernanda; Sember, Alexandr; Bertollo, Luiz Antônio Carlos (Genes, 2017)
Abstract: Fishes exhibit the greatest diversity of species among vertebrates, offering a number of relevant models for genetic and evolutionary studies. The investigation of sex chromosome differentiation is a very active and striking research area of fish cytogenetics, as fishes represent one of the most vital model groups. Neotropical fish species show an amazing variety of sex chromosome systems, where different stages of differentiation can be found, ranging from homomorphic to highly differentiated sex chromosomes. Here, we draw attention on the impact of recent developments in molecular cytogenetic analyses that helped to elucidate many unknown questions about fish sex chromosome evolution, using excellent characiform models occurring in the Neotropical region, namely the Erythrinidae family and the Triportheus genus. While in Erythrinidae distinct XY and/or multiple XY-derived sex chromosome systems have independently evolved at least four different times, representatives of Triportheus show an opposite scenario, i.e., highly conserved ZZ/ZW system with a monophyletic origin. In both cases, recent molecular approaches, such as mapping of repetitive DNA classes, comparative genomic hybridization (CGH), and whole chromosome painting (WCP), allowed us to unmask several new features linked to the molecular composition and differentiation processes of sex chromosomes in fishes.
Keywords: simple and multiple sex chromosomes; alternative evolutionary models; independent and common origins; conventional and molecular cytogenetics